DETERMINATION OF A SIMPLE AND ROBUST METHOD TO CALCULATE IGNITION DELAY IN COMPRESSION IGNITION ENGINES: APPLICATION TO DIESEL-BIODIESEL-ETHANOL BLENDS - Bret, P.; Pradelle, F. (Revista de Engenharia Térmica, 2023)
Today, the automobile industry is under increasing pressure from governments and environmental organizations to lower their carbon footprint. Car manufacturers release new models that follow modern and severe norms of pollutant emissions using eco-friendly technologies. Their strategy follows two main pathways: decarbonization and increase of efficiency. In order to achieve the aforementioned objective, the replacement of fossil fuels with renewable biofuels with lower carbon footprints, such as biodiesel and/or ethanol, contribute to the decarbonization of current internal combustion engines. However, changes in the fuel composition also imply some adjustments in the injection and combustion settings to optimize the engine operation. An important parameter to assess the combustion process in a compression ignition (CI) engine is the ignition delay (ID), defined as the duration between the start of fuel injection (SOI) and the start of combustion (SOC). Different direct and indirect approaches are reported in the literature to measure or calculate the ID. This study investigates two indirect methods based on the measurement of the indicated pressure inside the combustion chamber, throughout the displacement of the piston. These measurements are based on the position of the maximum of the third-order derivative of pressure as a function of the crank angle and the subjective shift from a polytropic compression process, respectively. The objective of the present work is to define an objective criterion to quantify this shift in order to allow a unique determination of the ID, independently of the adopted method. Thus, data of six different fuel blends of diesel-biodiesel-ethanol in a four-stroke CI engine from tests performed at PUC Rio’s Vehicular Engineering Laboratory for different loads and engine speeds were analyzed using the software Matlab. As observed in previous literature, the results show that the addition of biodiesel and ethanol concentration in the blends slightly increases the ID. Moreover, the difference between the experimental pressure with combustion and the calculated pressure in the polytropic compression process at the SOC position is lower as engine load increases and/or engine speed decreases and seems independent of the fuel blend composition. Nonetheless, the variation of the pressure difference at the SOC stays moderate, allowing the determination of a unique value to directly read the ID from the indicated pressure profile, without requiring the smoothing process of the third-order derivative of the pressure.